2005
DOI: 10.1136/adc.2004.067918
|View full text |Cite
|
Sign up to set email alerts
|

Silver nitrate burns following umbilical granuloma treatment

Abstract: Aims: To study the relation between the use of parent reported home smoking bans and smoke exposure among children aged 18-30 months. Methods: A total of 309 smoking households with children aged 18-30 months, who were part of the Coventry Cohort study, consented to participate in this cross-sectional survey. Results: Although parents in almost 88% of smoking households reported using harm reduction strategies to protect their toddlers from smoke exposure, only 13.9% reported smoking bans in the house. Mean lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Silver nitrate has antiseptic, shrinking, and caustic features depending on the concentration and duration of application. Several disadvantages of this treatment modality have been reported including the requirement for treatment by health care personnel at hospitals, the need to apply the treatment more than once, and complications such as the development of discolorations, burns or necrosis in the skin unless care is exercised (Daniel 2001;Majiga et al, 2005). In our study, 23.3% of the first group were needed to apply silver nitrate twice.…”
Section: Discussionmentioning
confidence: 64%
“…Silver nitrate has antiseptic, shrinking, and caustic features depending on the concentration and duration of application. Several disadvantages of this treatment modality have been reported including the requirement for treatment by health care personnel at hospitals, the need to apply the treatment more than once, and complications such as the development of discolorations, burns or necrosis in the skin unless care is exercised (Daniel 2001;Majiga et al, 2005). In our study, 23.3% of the first group were needed to apply silver nitrate twice.…”
Section: Discussionmentioning
confidence: 64%
“…For this reason, literature advices a more conservative approach to the infective complications of the umbilical area (granuloma) such as a 70% alcohol treatment. 20,21 Regards to caregivers' perception about the UC care, the research highlighted no differences between the experimental and control group us in satisfaction with management and results of the treatment and in anxiety reported by mothers at home. The few cases that expressed a scarce satisfaction with dry cord care were not connected to the onset of complications, but only to scepticism among an experimental treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, this method carries a risk of chemical burns, and caution should be exercised. [7][8][9] Applying white soft paraffin around the umbilical granuloma at the time of cauterisation is a proposed method to reduce the risk of chemical burns. 7 Although limited, evidence suggests that some granulomas resolve with conservative management alone, using simply alcohol wipes or salt application at each nappy change.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although limited, evidence suggests that some granulomas resolve with conservative management alone, using simply alcohol wipes or salt application at each nappy change. [7][8][9][10][11][12] Numerous small and low level evidence studies have found that in 90-100% of cases the use of common table salt alone leads to the resolution of umbilical granulomas. [10][11][12] Two small studies (n=50), in Saudi Arabia and Bangladesh, showed high resolution rates with the application of salt for 30 minutes after cleaning twice daily for 3-5 days.…”
Section: Discussionmentioning
confidence: 99%